2009
DOI: 10.1007/s12028-008-9182-8
|View full text |Cite
|
Sign up to set email alerts
|

HHH Regime for Arteritis Secondary to TB Meningitis: A Prospective Randomized Study

Abstract: HHH therapy is safe and may be beneficial in the management of patients with infective arteritis secondary to TBM. Further study in a larger group with improved monitoring of cerebral circulation is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…63,66,68 A small preliminary study has tentatively suggested that a hypervolaemiae hyperfusionehaemodilution (HHH) regime used in the treatment of vasospasm complicating subarachnoid haemorrhage (SAH) may improve focal deficits and altered mental status in patients with TBM and arteritis. 91 The study was predicated on the hypothesis that arteritis in TBM resembles this complication of SAH syndromically and pathologically e both are basal meningeal disorders with similarities in perforating vessel pathology and resulting ischaemia. The results were equivocal but merit further investigation.…”
Section: Treatmentmentioning
confidence: 99%
“…63,66,68 A small preliminary study has tentatively suggested that a hypervolaemiae hyperfusionehaemodilution (HHH) regime used in the treatment of vasospasm complicating subarachnoid haemorrhage (SAH) may improve focal deficits and altered mental status in patients with TBM and arteritis. 91 The study was predicated on the hypothesis that arteritis in TBM resembles this complication of SAH syndromically and pathologically e both are basal meningeal disorders with similarities in perforating vessel pathology and resulting ischaemia. The results were equivocal but merit further investigation.…”
Section: Treatmentmentioning
confidence: 99%
“…Triple H therapy (hypervolemia, hypertension, and hemodilution) is effective for arteritis secondary to tuberculous meningitis, 7) and administration of corticosteroid and/or antibiotics is effective. 20,23) In our case, the clinical symptoms progressed despite antibiotic administration with hypervolemic therapy, hyperdynamic therapy, and corticosteroid administration.…”
Section: Discussionmentioning
confidence: 99%
“…These different options need to be addressed. Few trials have been conducted evaluating high doses of rifampicin and use of fluoroquinolones for TBM (Heemskerk 2016; Ruslami 2013; Thwaites 2011). However, these trials assessed survival as main outcome and did not follow-up participants after completion of ATT for relapse.…”
Section: Authors' Conclusionmentioning
confidence: 99%